The evolution of contentious administrative procedural law in Costa Rica. A journey through the doctrine published in the “Revista de Ciencias Jurídicas” - Víquez Cerdas, Cristina (2023)
This essay aims to take a journey through the legal studies published in the “Revista de Ciencias Jurídicas” in its sixty years of existence, with the objective of reflecting on the evolution of the Administrative Litigation Process in Costa Rica.